Profile of Blood Pressure Control and Other Comorbidities Among Medical Outpatients Attending A University Teaching Hospital, South-South Nigeria - Umuerri, Ejiroghene Martha; Ohaju-Obodo , JO; Aiwuyo , HO; Aigbe, FI (African Journal of Tropical Medicine and Biomedical Research, 2019)
Background: Hypertension is the commonest non-communicable diseases worldwide. Patients suffering from this condition may also have other co-morbidities. Aim: To show the profile of blood pressure control among patients attending the Consultant Medical Out-Patient Department (MOPD). Methodology: A retrospective descriptive study of MOPD clinic attendees with hypertension. Patients aged 18 years and above who had both their first and sixth clinic visits between November 2012 and November 2013 were recruited for the study. Results: A total of 150 subjects were enrolled with a mean age 58.3±13.0 years, and 68 (45.3%) were males. The mean SBP, DBP and pulse rates at first and sixth visits were 145.8(±23.3) mmHg, 87.8(±14) mmHg and 83.1(±15.1) bpm, and 138.0(±22.9) mmHg, 84.5(±12.9) mmHg and 80.9(±13.4) bpm, respectively. By the third clinical visit, 67% of the study population had attained target blood pressure control. One hundred and fourteen (76.0%) of the study population had co-morbidities and complications (diabetes, dyslipidemia, heart failure, hypertensive heart disease). All the patients with dyslipidemia were placed on lipid lowering drugs but no repeat test was done during the study period. About 7.3% of the population had adverse drug reactions such as headaches, dizziness, generalized body pains and nausea. Conclusion: Only 67% of the subjects attained target blood pressure control by the third visit. There is need for more aggressive approach in managing patients with hypertension. It is important to document adverse drug reactions and follow the recommended pharmacovigilance protocol.